(untitled) (Journal of the College of Basic Education, 2022)
Most of the time, the major characters in a literary work especially the protagonist is assumed to be, at least, another image of the author. So, the leading character in the novella is another replica of Conrad. He, both in reality and in fiction, plays the main role in the journey to the dark continent and enriches the novella with his rational observations. The journey of 1890 Conrad participated in Congo has transformed him into a distorted, full of wounds, emotionally defeated, and sick. Marlowe was very enthusiastic and attempted to polish the ugly picture of imperialism. Therefore, before the journey, he had clashing views that turned the readers skeptical about Marlow’s story, especially in the first part of the novella. He has come through violence, the danger of nature, the inability to sense reality, and ethical obscurity. Marlow’s unreliability came from his views which are told several times by different characters. He supports the imperialistic and racial views when he called conges primitives. Even some characters in his journey are unnamed during the trip. This will make readers observe that some incidents, tendencies, feelings, and reactions are not authentic and unreliable because of the narrator’s unreliability. Throughout the novella, Marlow’s attitudes stand, and views fluctuate and do not meet the readers’ expectations. This kind of fluctuation creates a sense of uneasiness, which pervades the whole novella and make readers judge that Marlow is an unreliable narrator, who attempts to polish certain ugly images in novellas like Kurtz, Europe, company, and imperialism. Marlow was inconsistent in his narrative and there is no doubt that this inconsistency turns him to be unreliable especially when readers find this discrepancy because it destabilizes readers.